HISTORY OF CARDIAC AND THORACIC SURGERYA historical outline of surgical treatment for congenital chest wall deformities - Pawlak, Krystian; Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
This paper presents the most important events concerning the surgical treatment of congenital chest wall deformities from the early twentieth century to current times. This historical outline features the most deserved and most prominent surgeons in this field, such as F. Sauerbruch, M. Ravitch, D. Nuss, and others. We also recall the Polish pioneers of the surgical treatment of chest wall deformities, including M. Rzepecki, R. Drews, and J. Fibak, at the same time referring to contemporary experiences.